Developing Constipation: Dietary Fiber, Western Disease, and Industrial Carbohydrates. Issue 2 (2nd July 2016) - Gil-Riaño, Sebastián; Tracy, Sarah E.
Abstract: This paper focuses on the rise of what we call the dietary fiber paradigm, as championed by British medical researcher Denis Burkitt, a.k.a. "Dr Fiber, " and his collaborators working in Uganda and South Africa. We situate this attention to fiber intake in nutritional advice within a longer history of white Euro-American anxieties about the corrosive physiological effects of modernization. We examine how former colonial medical experts transformed dietary fiber from an object of negligible nutritional value – mere "roughage" – to one whose presence could mean the difference between health and disease. In the 1960–70s, Burkitt and his collaborators developed the concept of Western "diseases" to describe a series of chronic bodily ailments they linked to modern culinary infrastructure, or the consumption of what they called "refined carbohydrates" – particularly, commercially produced white bread. Chief among these were afflictions of the intestinal tract: diverticulosis coli, colon and bowel cancer, ulcerative colitis, and appendicitis. Startled by the observation that colonic disorders were practically absent in the "Third World" yet ubiquitous in modern affluent societies, these researchers hypothesized that the transit-time in which food was consumed, digested, and evacuated could be used to track these disparities. Is digestive dysfunction a necessary by-product of industrialized food systems, they asked? Is constipation an unavoidable feature of modernity? Through hospital questionnaires and observational prison studies, Burkitt and others surveyed the bowel movements, stool size, and diets of a variety of racial groups in several African countries and in Britain, and identified dietary fiber as a prophylactic for the hazards of modern eating. Burkitt's influential studies, we suggest, tell a resonant story of culinary modernization gone wrong – of a corrosive disconnect between the architecture of the human gastrointestinal tract and that of the quickly absorbed carbohydrates refined for purity and for whiteness.